2021
DOI: 10.1186/s12933-020-01201-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of insulin resistance on subclinical left ventricular dysfunction in normal weight and overweight/obese japanese subjects in a general community

Abstract: Background Insulin resistance carries increased risk of heart failure, although the pathophysiological mechanisms remain unclear. LV global longitudinal strain (LVGLS) assessed by speckle-tracking echocardiography has emerged as an important tool to detect early LV systolic abnormalities. This study aimed to investigate the association between insulin resistance and subclinical left ventricular (LV) dysfunction in a sample of the general population without overt cardiac disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 45 publications
4
11
0
Order By: Relevance
“…Both the Coronary Artery Risk Development in Young Adult (CARDIA) and Framingham Heart Study (FHS) Offspring and 3rd generation cohorts, 3179 and 6231 participants respectively, found that higher HOMA-IR was associated with worse LVLS, a finding that persisted after adjustment for waist circumference [ 14 , 15 ]. Similar results were observed in a smaller study of 539 Japanese participants [ 26 ]. Additionally, the CARDIA study also found that higher HOMA-IR was also associated with worse LVDSR [ 14 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Both the Coronary Artery Risk Development in Young Adult (CARDIA) and Framingham Heart Study (FHS) Offspring and 3rd generation cohorts, 3179 and 6231 participants respectively, found that higher HOMA-IR was associated with worse LVLS, a finding that persisted after adjustment for waist circumference [ 14 , 15 ]. Similar results were observed in a smaller study of 539 Japanese participants [ 26 ]. Additionally, the CARDIA study also found that higher HOMA-IR was also associated with worse LVDSR [ 14 ].…”
Section: Discussionsupporting
confidence: 91%
“…The association between fasting glucose measures and adverse cardiac mechanics has been previously evaluated in population-based cohorts free of baseline cardiovascular disease but these comprised younger individuals and mainly focused on LVLS measures [ 14 16 , 26 ]. The mean participant age for these studies was between 50 and 60 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus decreases remarkably the survival probability in patients diagnosed with CHF, and the risk is strictly affected by diabetes evolution and the level of glucose control over time. Insulin resistance carriers increased risk of heart failure as observed in early stage in patients without evidence of overt cardiac disease [196]. Similar findings have also been found in individuals with apparently uncomplicated type 2 diabetes mellitus whose exercise tolerance was reduced [197].…”
Section: Diabetes Mellitus and Insulin Resistance In Chfsupporting
confidence: 67%
“…Insulin is used in approximately one-third of patients with diabetes ( Trief et al, 2016 ), and it has emerged as an independent risk factor for left ventricular dysfunction ( Hirose et al, 2021 ) and heart failure hospitalizations ( Nichols et al, 2004 ; Wang et al, 2015 ). In addition to insulin causing sodium retention and being indicative of a more advanced diabetic state ( Cosmi et al, 2018 ), our findings suggest that it can inflict direct adverse changes to the left ventricular tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin use, which is common in up to one-third of DM patients ( Trief et al, 2016 ), is an independent risk factor for the development of heart failure ( Nichols et al, 2004 ; Wang et al, 2015 ) and LV dysfunction ( Hirose et al, 2021 ). Moreover, among patients with systolic heart failure, insulin therapy was associated with a higher 1-year mortality rate ( Smooke et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%